Questionable Requirement for Consent in Observational Research in Psychiatry - Hem, Marit Helene (Nursing ethics, 2007)
Informed consent represents a cornerstone of the endeavours to make health care research ethically acceptable. Based on experience of qualitative research on power dynamics in nursing care in acute psychiatry, we show that the requirement for informed consent may be practised in formalistic ways that legitimize the researcher's activities without taking the patient's changing perception of the situation sufficiently into account. The presentation of three patient case studies illustrates a diversity of issues that the researcher must consider in each situation. We argue for the necessity of researchers to base their judgement on a complex set of competencies. Consciousness of research ethics must be combined with knowledge of the challenges involved in research methodology in qualitative research and familiarity with the therapeutic arena in which the research is being conducted. The article shows that the alternative solution is not simple but must emphasize the researcher's ability to doubt and be based on an awareness of the researcher's fallibility.